Struktur Koneksi Matematis pada Siswa Climber dalam Menyelesaikan Masalah SPLTV (Jurnal Inovasi Pendidikan Matematika (JIPM), 2023)
The structure of the mathematical connection is an illustration the students' steps in building mathematical connections. This study aims to analyze the structure of the mathematical connection of climber students in solving the problems of the Linear Equation System Three Variable. This research is a qualitative research. The subjects of this study were 2 students of class XI SMA Negeri 1 Salaman. The technique of taking the subject is using purposive sampling. Data collection techniques used mathematical connection ability tests, field notes, and interview. The instruments used mathematical connection ability test, and interview guide. The results showed that the mathematical connection structure of climber students in solving LESTV problems fulfilled four components in building mathematical connections, namely starting with mathematical understanding where climber students were able to recognize mathematical ideas by understanding information from the questions. Both mathematical representations, by being able to represent in the form of a linear equation of three variables by connecting between mathematical ideas. The third is mathematical connections, where climber students can connect ideas from linear equations of three variables to get a solution. Fourth, there is mathematical reasoning, with climber students being able to relate and use concepts in LESTV material that are interconnected to produce a coherent whole.